Siddha and Ayurvedic management of Ovarian Cyst: A case study - Vijitha, P.; Sritharan, G.; Anpuchelvi, S. (University of Colombo, Sri Lanka, 2023)
Ovarian cysts are common finding in general gynecology. An ovarian cyst is one of the most common causes of ovarian dysfunction, which has a direct impact on fertility. A female patient aged 18 visited the outpatient clinic of the Herbal Health Care Centre in Jaffna, Sri Lanka, on 19.01.2021, with lower abdominal pain for two years, reduced menstrual intervals for one year, and pain in the right lower quadrant. She reported having experienced localized soreness a few months back. There was a sudden onset of pain without any prior history. The left ovarian cyst (size-43 mm) in an ultrasound scan reported. The laparoscopic approach for removing the cyst. The woman had somewhat recovered from her ovarian cyst symptoms, nevertheless. Then the left ovary had a 14mm cyst, per the results of the ultrasound scan that was done on 2019. According to the ultrasound scan obtained on 2020, as depicted in, the cyst was gradually expanding and had grown to a diameter of 23 mm. At the patient's request, the doctors affiliated with the herbal health care centre began the Siddha Ayurvedic course of treatment given Sathavary (Asparagus racemosus) decoction 60 ml twice a day, before meal, Karisalai (Eclipta alba) syrup 20ml twice a day after meal. Tripala tablet 2, twice a day after meal. Kanchanara guggulu 2 twice a day after meal. The patient has seen a demonstration of Kayakalpha exercise. There are two exercises in it. Aswini Mudra and Ojus Breath are among them. On September 1, 2021, the ninth day of the most recent menstrual cycle, an ultrasound examination was carried out six months after the patient had begun treatment. According to the report, the left ovary was normal in size and appearance, and the ovarian cyst had shrunk in size. This case study serves as an example of how Siddha Ayurvedic medicine can effectively treat ovarian cysts without the need for surgery.
Keywords: Ovarian cyst; Sri Lanka; Karpa vaayu; Tridoshasa